2002
DOI: 10.1001/archneur.59.7.1133
|View full text |Cite
|
Sign up to set email alerts
|

Down Syndrome and Alzheimer Disease

Abstract: Acetylcholinesterase inhibitors may be helpful in reversing the symptoms of dementia during early and middle stages of cognitive decline. These findings support the rationale for a more extensive study of the efficacy of acetylcholinesterase inhibitors in Down syndrome dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 15 publications
4
41
1
1
Order By: Relevance
“…However, despite considerable theoretical reasons to suggest patients with DS, especially those with concurrent dementia, could derive benefit from cholinesterase inhibitor therapy, there are currently few studies reported in the literature from which to draw a conclusion. Some authors claim improvement in socialisation subscale and adaptive behaviour composite score (Kishnani et al, 1999) in patients with DS with or without dementia (Lott et al, 2002;Prasher et al, 2002). Others report no clinical benefit and frequent adverse effects (Cipriani et al, 2002;Hemingway-Eltomey and Lerner, 1999).…”
Section: Drugs To Improve Cognitionmentioning
confidence: 99%
“…However, despite considerable theoretical reasons to suggest patients with DS, especially those with concurrent dementia, could derive benefit from cholinesterase inhibitor therapy, there are currently few studies reported in the literature from which to draw a conclusion. Some authors claim improvement in socialisation subscale and adaptive behaviour composite score (Kishnani et al, 1999) in patients with DS with or without dementia (Lott et al, 2002;Prasher et al, 2002). Others report no clinical benefit and frequent adverse effects (Cipriani et al, 2002;Hemingway-Eltomey and Lerner, 1999).…”
Section: Drugs To Improve Cognitionmentioning
confidence: 99%
“…22 However, the development of Eisenmenger syndrome in association with ventricular septal defect will still lead to significant limitations in health and longevity. Interestingly, the most significant health risk for people with Down syndrome over 40 years of age has been identified as Alzheimer's disease (AD).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the most significant health risk for people with Down syndrome over 40 years of age has been identified as Alzheimer's disease (AD). 22 After 35 years of age, virtually all individuals with Down syndrome have developed the neuropathologic characteristics of AD, although a smaller percentage undergo symptoms of cognitive decline. 22 The general dental practitioner should be aware of the possible onset of clinical symptoms of AD, since adult patients may experience memory loss, be difficult to manage behaviourally in the clinical setting, and the level of home care may decline.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution factor (R s ) was calculated by R s = 1/4 (a -1) ( ber and k' is the average retention factor for the two bands. The column plate number was determined using the formula, N = 5.54 (t R /w h ) 2 , where w h is the bandwidth at 50 % of peak height.…”
Section: Peak Characteristicsmentioning
confidence: 99%